A Cross-Canada Surveillance of Antimicrobial Resistance in Respiratory Tract Pathogens - Ross J Davidson; Canadian Bacterial Surveillance Network; Donald E Low (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the prevalence of antimicrobial resistance in clinical isolates of Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis from medical centres across Canada.